Malay numeral classifier usage in caretaker-child talk - Khazriyati Salehuddin; Winskel, Heather (Penerbit UKM, 2012)
To the nativists and cognitivists, input plays a minor role in language acquisition;however, more recent studies have shown that to a certain extent, the frequency and usage of lexical terms in children’s linguistic environment do play a role in language development, especially when they involve interaction. This paper presents an investigation on the usage of eight Malay shape-based numeral classifiers in eleven caretaker-child interactions. A semi-structured elicited procedure was designed to stimulate the caretaker and child to interact with each other in a naturalistic setting. Since Malay numeral classifiers are most prominently observed in counting activities, an interactive game was designed to identify what numeral classifiers caretakers would choose to talk about more in a situation where all numeral classifiers had the same chance to be talked about. Caretakers’ usage of numeral classifiers and their reactions to children’s usage of numeral classifiers are highlighted in this paper. Results indicate that Malay numeral classifier usage is not pervasive in Malay caretaker-child interactions. They suggest that the degree of obligatoriness of numeral classifiers in the Malay grammar plays a role in caretakers’ numeral classifier usage and their reactions to children’s usage.